Plasma Membrane Redox Enzyme Is Involved in the Synthesis of O2- and H2O2 by Phytophthora Elicitor-Stimulated Rose Cells. - Auh, C. K. (1995)
An elicitor prepared from the autoclaved cell walls of Phytophthora sp. induced O2- generation and H2O2 accumulation by cultured cells of Rosa damascena Mill. cv Gloire de Guilan. N,N-Diethyldithiocarbamate, a superoxide dismutase inhibitior, blocked H2O2 accumulation and caused a dramatic accumulation of O2- by elicitor-treated rose cells. In the absence of N,N-diethyldithiocarbamate no detectable O2- was accumulated. Diphenyleneiodonium, quinacrine, pyridine, and imidazole, inhibitors of the mammalian neutrophil NADPH oxidase responsible for the generation of O2- during phagocytosis, inhibited O2- generation by elicitor-treated rose cells. Diphenyleneiodonium also inhibited NADH-dependent O2- production by plasma membranes isolated from rose cells. None of the four compounds inhibited the peroxidase activity in the cell-suspension medium. These results demonstrate that elicitor-stimulated accumulation of H2O2 comes only from superoxide dismutase-catalyzed dismutation of O2-. The data are inconsistent with the hypothesis that the synthesis of O2- is catalyzed by extracellular peroxidase and suggest that the enzyme responsible for the synthesis of O2- by elicitor-treated rose cells might be similar to the mammalian neutrophil NADPH oxidase.